Development and Initial Validation of the Disruptive Mood Dysregulation Disorder Questionnaire Among Adolescents From Clinic Settings - Boudjerida, Assia; Labelle, Réal; Bergeron, Lise; Berthiaume, Claude; Guilé, Jean-Marc; Breton, Jean-Jacques (Frontiers in Psychiatry, 2022)
Abstract: Objectives: Disruptive mood dysregulation disorder (DMDD) is a new DSM-5 diagnosis. It is observed in youths and is characterized by chronic irritability and temper outbursts. This study aimed i) to develop a brief questionnaire administered during a semi-structured interview and ii) to assess its psychometric properties with adolescents 12 to 15 years old by estimating its internal consistency and its concurrent association with measures of depressive symptoms and borderline personality traits. Methods: A 10-item questionnaire was developed based on the DSM 5 criteria and input from mental health professionals. The questionnaire was administered to 192 adolescents from youth centres, inpatient units and specialized outpatient clinics in Montreal, as were the Schedule for Affective Disorders and Schizophrenia for School-Aged Children (K-SADS-PL), the Abbreviated version of the Diagnostic Interview for Borderlines revised (Ab-DIB), and the Dominic Interactive for Adolescents-Revised (DIA-R). Results: A DMDD Questionnaire among adolescents from clinic settings is obtained. The content of the instrument’s items was initially developed based on DSM-5 criteria and expert judgment to ensure that this new instrument covered the theoretical concepts of DMDD in English and French. Twelve participants (6.3%) met nine or more criteria and 11 youths (5.7%) met the three main criteria of DMDD (A, C and D), which suggested the likely presence of DMDD. The total Cronbach's alpha was 0.90. In addition, the DMDD Questionnaire was significantly associated with depressive symptoms and borderline personality traits. Conclusion: The reliability and concurrent validity indices suggest that the questionnaire as a decision-support tool may be used with adolescents in clinical settings. It highlights that the DSM-5 DMDD criteria seems associated with depressive symptoms and borderline personality traits. Finally, future studies will be necessary to establish more robust calculations in relation to the validity and reliability of this questionnaire.